The neurobiological bases of autism spectrum disorders: the R451C‐neuroligin 3 mutation hampers the expression of long‐term synaptic depression in the dorsal striatum. (4th October 2017) - Martella, Giuseppina; Meringolo, Maria; Trobiani, Laura; De Jaco, Antonella; Pisani, Antonio; Bonsi, Paola
Abstract: Autism spectrum disorders (ASDs) comprise a heterogeneous group of disorders with a complex genetic etiology. Current theories on the pathogenesis of ASDs suggest that they might arise from an aberrant synaptic transmission affecting specific brain circuits and synapses. The striatum, which is part of the basal ganglia circuit, is one of the brain regions involved in ASDs. Mouse models of ASDs have provided evidence for an imbalance between excitatory and inhibitory neurotransmission. Here, we investigated the expression of long‐term synaptic plasticity at corticostriatal glutamatergic synapses in the dorsal striatum of the R451C‐NL3 phenotypic mouse model of autism. This mouse model carries the human R451C mutation in the neuroligin 3 (NL3) gene that has been associated with highly penetrant autism in a Swedish family. The R451C‐NL3 mouse has been shown to exhibit autistic‐like behaviors and alterations of synaptic transmission in different brain areas. However, excitatory glutamatergic transmission and its long‐term plasticity have not been investigated in the dorsal striatum so far. Our results indicate that the expression of long‐term synaptic depression (LTD) at corticostriatal glutamatergic synapses in the dorsal striatum is impaired by the R451C‐NL3 mutation. A partial rescue of LTD was obtained by exogenous activation of cannabinoid CB1 receptors or enhancement of the endocannabinoid tone, suggesting that an altered cannabinoid drive might underlie the deficit of synaptic plasticity in the dorsal striatum of R451C‐NL3 mice. Abstract : We report the loss of long‐term synaptic depression (LTD) in the dorsal striatum (DS) of the R451C‐NL3 mouse model of ASD, suggesting a substantial involvement of the DS in ASD pathophysiology. LTD expression could be partially rescued by CB1 receptor activation or by endocannabinoid tone enhancement. The incomplete rescue obtained by sustaining cannabinoid signaling suggests that the R451C‐NL3 mutation may result in DS dysfunction by causing alterations upstream to the endocannabinoid system.